Persepsi Peserta Didik Terhadap Sikap Diskriminatif Guru di SMP Negeri 4 Sengkang Kabupaten Wajo - Saputra, Rahim; Tahir, Ilyas; R, Muh Aidil Sudarmono; Mustamin, Mustamin; Wahab, Abdul (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study examines the discriminatory practices of teachers in class VIII.A of SMPN 4 Sengkang, Wajo Regency, and its impact on students. The aim is to identify the factors causing discrimination, students' perceptions of teacher treatment, and strategies for handling it. This descriptive qualitative study used observation, interviews, and documentation, involving the principal, teachers, and students as informants. The results showed that the perceptions of students, both male and female, were uniform: there was teacher discrimination that was considered unfair. This discrimination is often rooted in subjective assessments of teachers, influenced by personal closeness to certain students. Schools try to address this problem through teacher meetings, coaching, and teacher performance evaluations. However, the implementation and supervision of these efforts need to be improved to create a fair and inclusive learning environment for all students.